2021
DOI: 10.1101/2021.02.25.432728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronos: a CRISPR cell population dynamics model

Abstract: CRISPR loss of function screens are a powerful tool to interrogate cancer biology but are known to exhibit a number of biases and artifacts that can confound the results, such as DNA cutting toxicity, incomplete phenotype penetrance and screen quality bias. Computational methods that more faithfully model the CRISPR biological experiment could more effectively extract the biology of interest than typical current methods. Here we introduce Chronos, an algorithm for inferring gene knockout fitness effects based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 39 publications
(64 reference statements)
1
45
0
Order By: Relevance
“…The copyright holder for this preprint this version posted December 16, 2021. ; https://doi.org/10.1101/2021.12.15.472866 doi: bioRxiv preprint the DepMap dataset [40][41][42][43][44], we found that 801 of 1054 cell lines are dependent on METTL3 (dependency probability score > 0.5). Therefore most cells lines will not survive after METTL3 knockout.…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted December 16, 2021. ; https://doi.org/10.1101/2021.12.15.472866 doi: bioRxiv preprint the DepMap dataset [40][41][42][43][44], we found that 801 of 1054 cell lines are dependent on METTL3 (dependency probability score > 0.5). Therefore most cells lines will not survive after METTL3 knockout.…”
Section: Author Contributionsmentioning
confidence: 99%
“…To understand which cell lines require METTL3 for survival, we screened the Cancer Dependency Map Project (DepMap) 21Q4 dataset [40][41][42][43][44]. This dataset measures cell proliferation in 1054 cell lines following a CRISPR loss-of-function screen.…”
Section: Mettl3 Knockout Cell Lines Are Generally Not Viable 10mentioning
confidence: 99%
“…An inspection of CRISPR screening of 1054 cancer cell lines using DepMap showed that EXOSC1-10 and DIS3 (EXOSC11) are essential in most cancer cell lines (Figure 3a) [100,101]. PABPN1 and MTR4, as well as CBCA components and ZC3H18, also exhibit similar essentialness.…”
Section: Rna Exosome and Cancermentioning
confidence: 99%
“…Cellular dependency data was obtained from the DepMap Public 21Q3 dataset using the DepMap portal (depmap.org/portal). Gene knockout effects (CERES) from project Achilles CRISPR screens were obtained for BRCA1-wildtype cell lines and for cell lines bearing a deleterious mutation for BRCA1 in accordance to the Cancer Cell Line Encyclopedia Project (CCLE) (Dempster et al, 2019(Dempster et al, , 2021Meyers et al, 2017;Pacini et al, 2021). CHAF1A and HIRA gene effects were then plotted as a regression for BRCA1wildtype and BRCA-mutant samples.…”
Section: Quantification Of Gene Expression By Real-time Quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%